2005
DOI: 10.4314/ajpsy.v8i3.30192
|View full text |Cite
|
Sign up to set email alerts
|

Non-fatal suicidal behaviour at the Johannesburg General Hospital

Abstract: Objective: Non-fatal suicidal behaviour (NFSB) severely impacts on the health services and the resources of a country and should be prevented. The aim of this control study was to describe a group of patients with NFSB and to elicit, if any, the factors associated with this behaviour compared to a non-suicidal control group. Method: Interviews were conducted on patients with NFSB treated in the Johannesburg Hospital medical emergency rooms. The information was gathered by way of a questionnaire and included: p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 26 publications
(25 reference statements)
0
7
0
Order By: Relevance
“…13 The current increasing trend of patients presenting with non-fatal suicide in South Africa will further impact the nation's healthcare services and place added strain on the resources of South Africa. 12 Non-fatal suicide patients who present to a healthcare establishment frequently require medication, counselling, a social worker, psychology and psychiatric evaluation and therapy. 14 In South Africa, divergent cultural and religious perceptions of suicidal behaviour have also influenced the assumption that suicidal behaviour is not a significant problem in parts of Africa.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…13 The current increasing trend of patients presenting with non-fatal suicide in South Africa will further impact the nation's healthcare services and place added strain on the resources of South Africa. 12 Non-fatal suicide patients who present to a healthcare establishment frequently require medication, counselling, a social worker, psychology and psychiatric evaluation and therapy. 14 In South Africa, divergent cultural and religious perceptions of suicidal behaviour have also influenced the assumption that suicidal behaviour is not a significant problem in parts of Africa.…”
Section: Methodsmentioning
confidence: 99%
“… 11 Mental health issues, past history of deliberate self-harm, poor self-esteem and feeling of hopelessness are seen amongst patients presenting with non-fatal suicide. 12 Patients likely to cause deliberate self-harm have reported financial stress, interpersonal relationship problems, lack of tertiary education and past psychiatric illness as the main reasons contributing to suicidal behaviour. 13 The current increasing trend of patients presenting with non-fatal suicide in South Africa will further impact the nation’s healthcare services and place added strain on the resources of South Africa.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Men accounted for 31.1% ( n = 101, mean age = 26.1 years) of attempted suicide cases referred to clinical psychologists over a 12-month period in a single hospital (du Toit et al, 2008). Moosa, Jeenah, Pillay, Vorster, and Liebenberg (2005) reported that 39.5% ( n = 17) of all suicide attempters admitted to Johannesburg General Hospital over a 1-month period were male. A national survey of 4,351 SA adults suggested that the lifetime prevalence of suicide ideation, plans, and attempts among men was 8%, 3.3%, and 1.8%, respectively (Joe, Stein, Seedat, Herman, & Williams, 2008).…”
Section: Suicide and Self-harm Among Men In Samentioning
confidence: 99%
“…In the last 15 years, a number of descriptive general hospital-based studies have investigated the epidemiology of DSH in urban and rural hospitals in SA. 7,8,9,10,11,12,13,14 The methodological differences across these studies make it difficult to generalise findings; however, data suggest that self-poisoning is the most common method of DSH in SA.…”
Section: Introductionmentioning
confidence: 99%